2020
DOI: 10.1186/s12935-020-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SAPCD2 correlates with proliferation and invasion of colorectal carcinoma cells

Abstract: Background: Suppressor anaphase-promoting complex domain containing 2 (SAPCD2) is a novel gene playing important roles in the initiation, invasion, and metastasis of several malignancies. However, its role in colorectal carcinoma (CRC) still remains unclear. Method: In this study, we investigated the expression and biological function of SAPCD2 in CRC. Immunohistochemistry (IHC) for SAPCD2 was performed in 410 pairs of CRC specimens and corresponding normal epithelial tissues, and in 50 adenoma tissues. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…SAPCD2 (Suppressor anaphase-promoting complex domain containing 2) plays important roles in the initiation, invasion, and metastasis of several malignancies. Previous studies have shown that SAPCD2 expression was significantly higher in colon cancer tissues than in adenoma and normal epithelial tissues, and it significantly promoted cell proliferation, migration, and invasion both in vitro and in vivo [ 39 ]. SKA3 (spindle- and kinetochore-related complex subunit 3) is a component of the spindle- and kinetochore-related complexes and is essential for accurate timing of late mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…SAPCD2 (Suppressor anaphase-promoting complex domain containing 2) plays important roles in the initiation, invasion, and metastasis of several malignancies. Previous studies have shown that SAPCD2 expression was significantly higher in colon cancer tissues than in adenoma and normal epithelial tissues, and it significantly promoted cell proliferation, migration, and invasion both in vitro and in vivo [ 39 ]. SKA3 (spindle- and kinetochore-related complex subunit 3) is a component of the spindle- and kinetochore-related complexes and is essential for accurate timing of late mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, SAPCD2 has attracted great interest regarding its role in the context of cancer studies. SAPCD2 has been reported to be upregulated in various kinds of tumors, including breast cancer (34), gastric cancer (11), hepatocellular carcinoma (17), colorectal carcinoma (14), glioblastoma (19), nasopharyngeal carcinoma (15), lung adenocarcinoma (16), melanoma (18), and renal cell cancer (20). SAPCD2 further promotes progression and metastasis in different human types of cancer by activating the Wnt/b-catenin, JAK/STAT, TGF-b, MAPK, and NF-kB signaling pathways, all of which have been reported to play crucial roles in cancer progression and metastasis (35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…SAPCD2 located on human chromosome 9q42.3 encodes a 389-amino acid protein (42.3 kDa) with EF-Hand domain at the N-terminal and functional CC-domains at the C-terminus (13). Accumulating studies have reported that SAPCD2 is overexpressed in several types of human cancer, and that SAPCD2 overexpression promotes the proliferation, migration, and invasion of cancer cells by various mechanisms (11,(14)(15)(16)(17)(18)(19)(20). However, little is known about the clinical significance and functional role of SAPCD2 in fibrosarcoma, especially metastatic fibrosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of positively stained tumor cells was scored as 0 (negative), 1 (1 − 25%), 2 (26–50%), 3 (51–75%), and 4 (>75%). The two scores were multiplied, and the resulting immune-reactive score (IRS) (values from 0 to 12) was used to classify the samples into two categories: high (4–12) and low (1–3) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%